Proposing critical realism and second-generation environmental justice for advancing sacrifice zone analysis - Cobs-Munoz, Victor; Westerholt, René (Technische Universität Dortmund, 2025)
This article addresses the complex social-ecological challenges faced by sacrifice zones—territories subjected to severe environmental degradation and social injustices. Traditional environmental justice research, with its emphasis on distributive justice, often fails to capture the intricate dynamics of these often not-recognized areas. In light of these limitations, this article proposes a second-generation environmental justice approach, employing a critical realist paradigm, to identify sacrifice zones and explore their deeper causal mechanisms. This approach, which transcends the distributional focus of traditional research, reveals mechanisms commonly observed in these zones. These mechanisms enable and sustain environmental degradation and social injustices through dynamics such as economic exploitation, policy failures, and power imbalances. Intertwined within social-ecological systems, these dynamics create cycles of poverty, health disparities, and ecological harm. Moreover, the article offers a methodological reflection on the theoretical proposal and planning practices toward environmental justice. It concludes with recommendations for future research, emphasizing the importance of systemic change and inclusive policy-making to achieve environmental justice and sustainability.
Progress in environmental geography; 4(1)
Keywords: Sacrifice zones; Critical realism; Environmental justice; Social-ecological systems; Causal mechanisms; 710